Do neural correlates of face expertise vary with task demands? Event-related potential correlates of own- and other-race face inversion - Wiese, Holger (Frontiers in Human Neuroscience, 2013)
We are typically more accurate at remembering own- than other-race faces. This “own-race bias” has been suggested to result from enhanced expertise with and more efficient perceptual processing of own-race than other-race faces. In line with this idea, the N170, an event-related potential correlate of face perception, has been repeatedly found to be larger for other-race faces. Other studies, however, found no difference in N170 amplitude for faces from diverse ethnic groups. The present study tested whether these seemingly incongruent findings can be explained by varying task demands. European participants were presented with upright and inverted European and Asian faces (as well as European and Asian houses), and asked to either indicate the ethnicity or the orientation of the stimuli. Larger N170s for other-race faces were observed in the ethnicity but not in the orientation task, suggesting that the necessity to process facial category information is a minimum prerequisite for the occurrence of the effect. In addition, N170 inversion effects, with larger amplitudes for inverted relative to upright stimuli, were more pronounced for own- relative to other-race faces in both tasks. Overall, the present findings suggest that the occurrence of ethnicity effects in N170 for upright faces depends on the amount of facial detail required for the task at hand. At the same time, the larger inversion effects for own- than other-race faces occur independent of task and may reflect the fine-tuning of perceptual processing to faces of maximum expertise.